Risk of lethal vessel strikes to humpback and fin whales off the west coast of Vancouver Island, Canada - Nichol, Linda M.; Wright, Brianna M.; O'Hara, Patrick; Ford, John K. B. (Endangered Species Research, 2017)
Vessel strikes are a source of mortality and injury for baleen whales, which can have population-level impacts. Spatial analysis of whale and marine traffic distributions provides a valuable approach for identifying zones with high collision risk. We conducted 34 systematic aerial surveys to estimate humpback Megaptera novaeangliae and fin whale Balaenoptera physalus densities off the west coast of Vancouver Island, Canada, including approaches to major shipping lanes in Juan de Fuca Strait, a gateway to the ports of southern British Columbia and Washington State. To predict whale densities, we fit negative binomial generalized additive models (GAMs) to sightings data, incorporating survey effort as an offset, and depth, slope, and latitude as environmental covariates. Humpbacks were primarily observed on the continental shelf, with highest predicted densities along the shelf edge (~200 m isobath), whereas fin whales were primarily distributed west of the shelf break (>450 m depth). We combined GAM-predicted whale densities with vessel traffic data to estimate the relative risk of ship strikes. Since vessel speed is an important determinant of lethality, we also calculated the relative risk of lethal injuries, given the probability that a collision occurs. Humpbacks were most likely to be struck along the shelf edge, the inshore approaches to Juan de Fuca Strait, and within the strait itself. Fin whales were most likely to be struck in the offshore approaches to Juan de Fuca and inside the western portion of the strait. Our study is the first to assess ship strike risk in this region of high whale density and marine traffic use. We are grateful to the pilots, navigational officers, and support staff of Transport Canada's National Aerial Surveillance Program (NASP) and Environment Canada's Marine Aerial Reconnaissance Team (MART), whose expertise and enthusiasm ensured the success of our aerial surveys for cetaceans. We also thank the following individuals for their assistance during the aerial surveys as ...